2017
DOI: 10.1097/md.0000000000007852
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy and cardiovascular disease risk

Abstract: Background:Even though several studies comparing vasectomy and cardiovascular disease (CVD) risk have been reported, most are small series with conflicting results. However, the extent of the risk is still uncertain. We therefore explored whether an association exists between vasectomy and CVD incidence and mortality.Methods:We searched PubMed, Embase, Web of Science, and Cochrane Library databases for relevant studies published before January 2017. Multivariate adjusted odds ratio (OR) and associated 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…Bhatia et al [ 69 ] reported substantial increases in serum levels of cholesterol and triglycerides in rabbits that had undergone a vasectomy. However, a large number of studies have confirmed (including Clarkson's research) that there is no association between vasectomy and cardiovascular disease or related factors (even if the time after surgery exceeds 20 years) ( Table 3 ) [ 40 68 70 71 72 73 74 75 76 77 ]. These factors include body mass index, cholesterol, triglycerides, protein, albumin and high-density lipoprotein levels, and the ratio of globulin.…”
Section: Resultsmentioning
confidence: 99%
“…Bhatia et al [ 69 ] reported substantial increases in serum levels of cholesterol and triglycerides in rabbits that had undergone a vasectomy. However, a large number of studies have confirmed (including Clarkson's research) that there is no association between vasectomy and cardiovascular disease or related factors (even if the time after surgery exceeds 20 years) ( Table 3 ) [ 40 68 70 71 72 73 74 75 76 77 ]. These factors include body mass index, cholesterol, triglycerides, protein, albumin and high-density lipoprotein levels, and the ratio of globulin.…”
Section: Resultsmentioning
confidence: 99%
“…Doenças cardiovasculares (DCV), como doença arterial coronariana (DAC), infarto do miocárdio (IM) e acidente vascular cerebral, são causas significativas de mortalidade e morbidade na população em geral em todo o mundo. 2 A DAC é a causa mais comum de morte no mundo entre as doenças cardiovasculares. O PTEN tem um papel crítico na hipertrofia e sobrevida dos cardiomiócitos.…”
Section: Discussionunclassified
“…Cardiovascular diseases (CVD), such as coronary artery disease (CAD), myocardial infarction (MI), and stroke are significant causes of mortality and morbidity in the general population worldwide. 2 CAD is the most common cause of death worldwide among cardiovascular diseases. PTEN plays a critical role in cardiomyocyte hypertrophy and survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations